Sun International : moving to "We will rock you" (Part A) - Viedge, Conrad (SAGE Business Cases., 2018)
It was December 2016 and almost three years since Rob Collins had been appointed chief operating officer (COO) of Sun International. When Collins arrived at the organisation, he felt that there was a pervasive air of "nostalgia" for the heydays when Sol Kerzner led the group, and that it was in need of change. Since his arrival, he had implemented a number of changes, some of which were still in progress. As the year was nearing an end and people were slowing down in anticipation of their summer holidays, Collins took time out to tackle some of the reading on his desk, which he had set aside for "when he had time". As he paged through the Harvard Business Review, a leadership article caught his attention and prompted him to pause and reflect on the changes he had made at Sun International. Collins thought about the glory days epitomised by the Sun City "We Will Rock You" television advertisement, which had engaged everyone - customers and staff alike - so effectively in the 1980s . He asked himself what still needed to be done to ensure that the group fulfilled its vision and was able once again to "rock" its customers.